2014
DOI: 10.5301/ijao.5000323
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous Veno-Venous Hemofiltration Protocol with Anticoagulant Citrate Dextrose Formula a and a Calcium-Containing Replacement Fluid

Abstract: In this pilot study, CVVH using ACD-A for RCA and a Ca2+ -containing RF was safely and effectively used without a continuous Ca2+ infusion. This protocol is a promising solution for maintaining effective CRRT when intravenous calcium is in short supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…As an advantage over the widely used tri-sodium citrate (TSC) solution, ACD-A has both lower sodium content and less buffer generation after metabolism (2 molecules of bicarbonate per molecule of citrate in comparison with 3 from TSC). ACD-A solution (containing 113 mmol/l citrate) was given to achieve a calculated pre-filter citrate concentration in blood of 2.8 mmol/l [10] (i.e., 2.8/113 = 1/40 of blood flow). This citrate dose, while being lower than in some RCA protocols, has been widely used for safe and effective RCA CRRT, achieving filter iCa 2+ concentrations of around 0.35 mmol/l [10,13], and was felt to represent the best balance between effective anticoagulation and risk of the development of metabolic alkalosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an advantage over the widely used tri-sodium citrate (TSC) solution, ACD-A has both lower sodium content and less buffer generation after metabolism (2 molecules of bicarbonate per molecule of citrate in comparison with 3 from TSC). ACD-A solution (containing 113 mmol/l citrate) was given to achieve a calculated pre-filter citrate concentration in blood of 2.8 mmol/l [10] (i.e., 2.8/113 = 1/40 of blood flow). This citrate dose, while being lower than in some RCA protocols, has been widely used for safe and effective RCA CRRT, achieving filter iCa 2+ concentrations of around 0.35 mmol/l [10,13], and was felt to represent the best balance between effective anticoagulation and risk of the development of metabolic alkalosis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to citrate and calcium replacement solutions, calcium-free dialysate or pre-dilution replacement fluid are required to maintain effective anticoagulation during dialysis, hemodiafiltration or pre-dilution hemofiltration, thus increasing the expense and complexity. Conversely in post-dilution hemofiltration, conventional replacement solutions can spare the need for costly supplemental calcium infusions [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the calcium fluxes and balances would be different if calcium containing fluid would have been used. There are still units where this modality is applied [32,33] leading to a high dosage of citrate and higher amount of calcium-citrate complexes in effluent. Fifth, the changes of calcium and magnesium might relate to citrate dosages and levels of citrate when analyzing larger cohort of patients.…”
Section: +mentioning
confidence: 99%
“…31,38 Generally, because calcium interferes with the action of the citrate, calcium-free dialysate or replacement fluids are often used with citrate anticoagulation. 4 Some researchers, 39,40 however, have shown that citrate anticoagulation can be effective with the use of calcium-containing replacement fluids, eliminating the need for a separate calcium infusion.…”
Section: Wwwccnonlineorgmentioning
confidence: 99%
“…1,31 If citrate is infused as a solution, it can be infused as a mixture of a trisodium citrate solution and an acid-citrate-dextrose solution. 31,39 Whatever the choice of citrate, the citrate dose must be titrated to achieve effective anticoagulation.…”
Section: Wwwccnonlineorgmentioning
confidence: 99%